A new species of the spider genus Xenonemesia Goloboff and first record of X. platensis Goloboff from Brazil (Araneae, Mygalomorphae, Microstigmatidae) - Indicatti, Rafael Prezzi; Lucas, Sylvia Marlene; Brescovit, Antonio Domingos (Zootaxa, 2007)
Xenonemesia otti n. sp. (Microstigmatidae) is described from Viamão and X. platensis Goloboff newly recorded for the first time from Caçapava do Sul, both in the State of Rio Grande do Sul, Brazil.